PENGARUH PENGETAHUAN PERPAJAKAN, SANKSI STP PASAL 7 UU KUP, PENERAPAN E-SPT TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP TELUK BETUNG - ANI HERLINA (Business and Enterpreneurship Journal (BEJ), 2021)
Taxes are a source of state revenue used for national development in order to realize the welfare of all Indonesians. e-SPT application can be supported by tax knowledge that has been known by taxpayers themselves. Tax knowledge that is owned by taxpayers can be considered to be a factor in increasing tax compliance by taxpayers. The level of reporting / submission of tax returns realized from 2014-2016 is always decreased, but in 2017 realized SPT experienced a slight increase. However, in 2018 decreased again. This shows that compliance and awareness of taxpayers is still low in fulfilling their tax obligations in terms of reporting / submitting their annual tax returns.The purpose of this study is to prove the influence of tax knowledge, STP article 7 sanctions on the KUP Law and the application of e-SPT to the compliance of individual taxpayers at the Teluk Betung KPP. This research is a quantitative research. The population in this study exists on all individual taxpayers in the Betung Bay KPP. Data were analyzed using multiple linear regression analysis and tested using SPSS version 23 with the intent to determine the effect of independent variables on the dependent variable at a 95% confidence level (95% ( a = 0.05).The results of this study indicate that the variable taxation knowledge (X1), STP article 7 sanctions UU KUP (X2) and the application of e-SPT (X3) simultaneously influence f on individual taxpayer compliance (Y). Tax knowledge knowledge variable (X1) influences and partially positive significance on individual taxpayer compliance (Y), STP sanction variable article 7 of the KUP Law (X2) has no effect and is not significantly positive partially on personal taxpayer compliance (Y), and e-SPT implementation variable ( X3) partially positive and significant influence on individual taxpayer compliance (Y).Keyword : knowledge of taxation, STP sanction article 7 of the KUP Law, application of e-SPT, compliance of individual taxpayer